Working in the New Technologies Sector? Education for Employment of People with Disabilities - Gąciarz, Barbara (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
In the 21st century, economic changes have contributed to the increased significance of modern technology sectors, especially in IT, e-commerce, e-marketing, and UX design. The advancement in these industries requires specialized knowledge in programming, design, and technology implementation, opening doors for individuals with various disabilities. New forms of work, particularly remote work and assistive technologies, enable some individuals with disabilities to participate in the open job market. However, this necessitates acquiring specialized education and the necessary skills and competencies for individuals with disabilities. Higher education institutions offer such opportunities. Therefore, we aim to investigate how graduates working in fields related to emerging technologies assess the initiatives and activities undertaken at their universities to prepare them for the workforce.The study encompassed 11 graduates with disabilities and revealed the importance of continued support for educational programs. Facilitating communication between employers and individuals with disabilities emerged as crucial, fostering mutual understanding and enabling a more accessible work environment for individuals with disabilities.